Spatial Variation in Catchment Response to Climate Change Depends on Lateral Moisture Transport and Nutrient Dynamics. Issue 10 (3rd October 2022) - Stephens, C. M.; Marshall, L. A.; Johnson, F. M.; Ajami, H.; Lin, L.; Band, L. E.
Abstract: Future shifts in rainfall, temperature and carbon dioxide (CO2 ) will impact hydrologic and ecosystem behavior. These changes are expected to vary in space because water and nutrient availability vary with terrain and soil properties, with feedbacks on vegetation and canopy adjustment. However, within‐basin patterns and spatial dependencies of ecohydrologic dynamics have often been ignored in future scenario modeling. We used a distributed process‐based ecohydrologic model, the Regional Hydro‐Ecological Simulation System, as a virtual catchment to examine spatial and temporal variability in climate change response. We found spatial heterogeneity in Leaf Area Index, transpiration and soil saturation trends, with some scenarios even showing opposite trends in different locations. For example, in a drying scenario, decreased vegetation productivity in water‐limited upslope areas enhanced downslope nutrient subsidies so that productivity increased in the nutrient‐limited riparian zone. In scenarios with both warming and rising CO2, amplifying feedbacks between mineralization, vegetation water use efficiency and litter fall led to large increases in growth that were often strongest in the riparian area (depending on the coincident rainfall change). Modeled transpiration trends were determined by the competing effects of vegetation growth and changing water use efficiency. Overall, the riparian zone experienced substantially different (and even opposing) ecohydrologic trends compared to the rest of the catchment, which is important because productive riparian areas often contribute a disproportionate amount of vegetation growth, transpiration and nutrient consumption to catchment totals. Models that are spatially lumped, lack key ecosystem‐driving dynamics, or ignore lateral transport could misrepresent the complex ecohydrologic changes catchments could experience in the future. Plain Language Summary: Climate change is expected to impact vegetation, water availability and nutrient processes, along with their mutual feedbacks. Effects on the landscape will vary across space because of differences in local factors, including terrain and soil properties. We used a detailed ecohydrologic model that accounts for vegetation growth, nutrient cycling, and hydrologic processes to investigate how climate change impacts could vary across a catchment. We found that different parts of the catchment experienced different changes in behavior, with some examples of opposing trends for the same climate inputs. We attributed these differences to water and nutrient transport between different parts of the catchment. For example, vegetation growth reduced in the upper parts of the catchment under a drier future scenario, because there is limited water available for growth in these areas. This meant that less nutrients were consumed upslope, and water that flowed downhill after rain contained higher concentrations of nutrients. Higher growth was then enabled in riparian areas where water was not limiting, even with a drying climate. Many commonly used hydrologic models lack the necessary processes to capture such responses, which limits our understanding of climate change impacts on ecosystems and water resources. Key Points: We used a process‐based model to investigate how climate change impacts spatial patterns of catchment response and ecohydrologic feedbacks The same climate forcing produced different (and even opposing) trends in different locations, often due to lateral subsidy effects The strongest trends were often modeled in the highly productive riparian zone that disproportionately affects overall catchment response